Solubility and absorption rate enhancement of CO2 in K2CO3. Issue 2 (22nd January 2016) - Ramazani, R.; Mazinani, S.; Hafizi, A.; Jahanmiri, A.; Van der Bruggen, B.; Darvishmanesh, S.
ABSTRACT: The influence of addition of 2-(1-piperazinyl)-ethylamine (as a promoter) on the solubility and absorption rate of carbon dioxide (CO2 ) in aqueous potassium carbonate solution (as a main solvent) was investigated experimentally, using a vapor liquid equilibrium (VLE) equipment in temperatures from 303.15 to 323.15 K and CO2 initial partial pressures between 25 and 75 kPa. The experimental data showed that the addition of 2-(1-piperazinyl)-ethylamine to potassium carbonate solution results in a significant enhancement in the solubility and absorption rate of CO2 . The response surface methodology was applied to explore the relationship between independent parameters on the CO2 loading capacity of blended solution.